PERFORMANCE ANALYSIS OF GRHASIA MENTAL HOSPITAL TRAINING AND INSTALLATION DEVELOPMENT WITH BALANCED SCORECARD METHOD - Handayu, Tuti; Tjahjono, Prof. Dr. Heru Kurnianto; Hidayah, Dr. Dr. Nur (jfpublisher, 2022)
The Education Research and Development Installation of Grhasia Mental Hospital (RSJ) have never implement a performance measurement, then it is not known what extent the success of financial and non-financial management in achieving organization vision and goals. This research was conducted to analyze the performance of Training and Development Installation of RSJ Grhasia through balanced scorecard (BSC) method with 4 perspectives, called finance, customers, internal business processes, then learning and growth. This research is a descriptive research which is analyzed descriptively analytic. The quantitative data were obtained from secondary data and survey results from internal (employees) and external customers (practice students). The research results from financial perspective shows poor results for income level and effectiveness ratio. On the other hand, it shows good results for Cost Recovery Rate/CRR. Customer perspective that shows satisfied results on employee satisfaction level and good results on student satisfaction level with education and training installation services.